Acute Leukemias of Ambiguous Origin. Issue 3 (1st September 2015) - Porwit, Anna; Béné, Marie C.
Abstract: Objectives: This session of the Society for Hematopathology/European Association for Haematopathology Workshop focused on acute leukemias of ambiguous origin. Methods: We provide an overview of mixed-phenotype acute leukemia (MPAL) as recognized in the current World Health Organization classification and summarize diagnostic criteria for major categories of MPAL: B/myeloid, T/myeloid, B/T, and B/T/myeloid. Results: Most MPAL cases submitted were B/myeloid and T/myeloid MPAL, the most frequent types, but three cases of B/T MPAL were also submitted, and examples of all categories are illustrated. We emphasize that a comprehensive approach to immunophenotyping is required to accurately establish the diagnosis of MPAL. Flow cytometry immunophenotyping using a large panel of antibodies is needed as well as confirmatory immunohistochemical analysis and cytochemistry studies for myeloperoxidase and nonspecific esterase. We discuss technical issues in determining blast lineage and possible pitfalls in MPAL diagnosis. In particular, rare cases of B-acute lymphoblastic leukemia (B-ALL) can express myeloperoxidase but are otherwise consistent with B-ALL and should be treated as such. Last, we review the differential diagnosis between acute undifferentiated leukemia and acute myeloid leukemia with minimal differentiation. Conclusions: There was an agreement that diagnosis of MPAL can be challenging, especially if applied flow cytometry panels are not comprehensive enough.